The potential cholesterol-lowering and prebiotic effects of bamboo shoot dietary fibers and their structural characteristics. (1st December 2020) - Wu, Weijie; Hu, Jie; Gao, Haiyan; Chen, Hangjun; Fang, Xiangjun; Mu, Honglei; Han, Yanchao; Liu, Ruiling
Highlights: IDF had better adsorption capacity than the corresponding SDF from same species. Cholesterol-adsorption capacity of bamboo shoot dietary fiber was sensitive to pH. F. spathacea IDF had lower crystallinity & larger amorphous area than other species. IDF and SDF from F. spathacea showed potential prebiotic activities. IDF significantly enhanced the production of SCFAs by in vitro fermentation. Abstract: The physicochemical and physiological properties of soluble dietary fiber (SDF) and insoluble dietary fiber (IDF) from bamboo shoots were investigated in present study. IDF showed better adsorption capacity than the corresponding SDF from the same species. Microstructure observation results indicated that the surface of IDF was porous, whereas the SDF was relatively flat and compact. The cholesterol-adsorption capacities of IDF and SDF from Fargesia spathacea were relatively higher than the other species. Both SDF and IDF from F. spathacea showed potential prebiotic effects, although the Lactobacillus and Bifidobacterium promotion effects of SDF were relatively stronger than IDF. Compared with control, the concentration of total short chain fatty acids in IDF and SDF supplement groups were increased by 1.28 and 0.71 folds, respectively. These results suggested that F. spathacea dietary fibers with strong cholesterol-adsorption activity and prebiotic potential, could be used as a bioactive ingredient in functional foods production.